Dietary quality, sleep quality and muscle mass predicted frailty among Chinese postmenopausal women in Malaysia - Chan, Kai Sze; Chan, Yoke Mun; Chin, Yit Siew; Mohd Shariff, Zalilah (MDPI, 2022)
The older adult population is growing faster than any age group, which increases their risk of frailty. Studies conducted among older adult are relatively scarce in Malaysia, especially among Chinese postmenopausal women, who have the longest life expectancy. Thus, the present study aimed to determine the prevalence of frailty and its associated factors among Chinese postmenopausal women. A total of 220 eligible respondents were recruited, with information on sociodemographic background, comorbidities, dietary intake and lifestyle behaviour were obtained using a structured questionnaire, while anthropometry indicators were assessed according to standard protocol. Fasting blood was withdrawn for the analysis of serum 25(OH)D. Multinomial logistic regression was used to determine factors that predict pre-frailty and frailty. Prevalence of pre-frailty and prevalence of frailty were 64.5 and 7.3%, respectively, and most of the respondents presented with weak handgrip strength. Pre-frailty was prevalent among the younger population. Dietary quality was unsatisfactory among the respondents, and the majority of them presented with a high percentage of body fat. An increased dietary quality index (DQI), poor sleep and low muscle mass were factors that contributed to frailty. In conclusion, nutritional factors should be considered in developing health-related policies and programs in reducing and delaying the onset of frailty.